2018
DOI: 10.3389/fpsyg.2018.00402
|View full text |Cite
|
Sign up to set email alerts
|

Global Repetition Influences Contextual Cueing

Abstract: Our visual system has a striking ability to improve visual search based on the learning of repeated ambient regularities, an effect named contextual cueing. Whereas most of the previous studies investigated contextual cueing effect with the same number of repeated and non-repeated search displays per block, the current study focused on whether a global repetition frequency formed by different presentation ratios between the repeated and non-repeated configurations influence contextual cueing effect. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Prior research had shown that contextual cueing is influenced by the frequency with which a given repeated display appears in a given block of trials (with larger contextual-cueing effects for frequently repeated displays; cf. Tseng, Hsu, Tzeng, Hung, & Juan, 2011;Zang, Zinchenko, Jia, Assumpção, & Li, 2018). Given this, investigating the effects of expectations arising from the relative repetitions of repeated and nonrepeated displays on context-based guidance of search would require that the effects of absolute repetitions of individual targetdistractor arrangements are equated across the critical learning conditions.…”
Section: Experiments 1a: Baselinementioning
confidence: 99%
“…Prior research had shown that contextual cueing is influenced by the frequency with which a given repeated display appears in a given block of trials (with larger contextual-cueing effects for frequently repeated displays; cf. Tseng, Hsu, Tzeng, Hung, & Juan, 2011;Zang, Zinchenko, Jia, Assumpção, & Li, 2018). Given this, investigating the effects of expectations arising from the relative repetitions of repeated and nonrepeated displays on context-based guidance of search would require that the effects of absolute repetitions of individual targetdistractor arrangements are equated across the critical learning conditions.…”
Section: Experiments 1a: Baselinementioning
confidence: 99%
“…It was shown that only those participants who started with 100% repeated displays, showed contextual benefits in the subsequent task, suggesting that the contextual cueing effect was stronger when participants learned and obtained certain expectations/beliefs about the existence of statistical regularities (i.e., repeated displays). A recent study found that global repetition frequency formed by different presentation ratios between the repeated and non-repeated configurations influences contextual cueing effect (Zang et al, 2018;Zinchenko et al, 2018), further confirming that global expectations can further modulate contextual memories. Applied to the current findings, it is reasonable that once participants form some expectations about the environmental regularities (i.e., about the existence of repeated displays), it is easier to acquire new contextual associations.…”
Section: Discussionmentioning
confidence: 69%
“…However, in contrast to Experiment 1, no contextual cueing was observed when both reference frames yielded invalid predictions ( Ego–/Allo– ). This was expected if participants relied more on the external reference frame (and less on allocentric information from the search display itself) because of the frame's higher overall validity (Zang et al, 2018 ).…”
Section: Interim Discussionmentioning
confidence: 99%
“…As mentioned, in Experiment 1, the allocentric reference frame had a low predictiveness of the target location and therefore might not have been used to retrieve memory traces of repeated displays. Apparently, the increased validity of the external reference frame prompted its use for search guidance in repeated displays (Zang et al, 2018 ). Note, this difference cannot be due to learning because the learning phases of Experiments 1 and 2 did not differ in validity.…”
Section: Discussionmentioning
confidence: 99%